Disiplin Pegawai Sebagai Mediator Antara Remunerasi, Supervisi, Komitment Pegawai terhadap Prestrasi Kerja - Hermanus Ren Lumentus Djula; Rulinawaty Rulinawaty; Usman Pakasi (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to examine factors that are predicted to influence the success or failure of the performance of Dishub civil servants, discuss the suitability of the ongoing TPP program, and examine changes that occur in the performance of Papua Dishub civil servants pre and post-implementation of Papua Provincial Gubernatorial Regulation No.31/2022 concerning the Second Amendment to the Top. Papua Gubernatorial Regulation No.6/2022 concerning Additional Electronic-Based Income for ASN in the Provincial Government Environment. Papua Fiscal Year 2022. This type of research is qualitative research. The research results show that the success factor for pre-TPP performance is due to the presence of complete work facilities. The ongoing system of providing TPP via electronic information has achieved an element of justice where officials and ASN can find out the reasons for receiving TPP and not receiving TPP in real-time and based on the ratio of output and input from the results of their work. The changes that occurred in the performance of civil servants at the Papua Transportation Department after the implementation of the TPP were a decrease in the quality of work, such as many work errors occurring due to work stress which arose due to the high workload ratio and the relatively very short time for completing the workload in obtaining the TPP. In conclusion, complete work facilities can increase discipline, while a conducive work environment can increase work comfort, this has a good impact on performance. Meanwhile, the failure factor is due to income that is not sufficient to meet needs Keywords: Discipline, Commitment, Employees, Work Performance, Remuneration, Supervision.